Diagnosis by axilla skin biopsy in an early case of Lafora's disease. Issue 11 (November 1992) - Rubio, G; Garcia Guijo, C; Mallada, J J; Cabello, A; Garcia Merino, A
Abstract : Myoclonus, seizures and progressive dementia are the main clinical features in Lafora's disease. This is the first reported case in which the diagnosis has been made by axillary skin biopsy in a patient with myoclonus but no other neurological symptoms.